Structural and Design Values of Solid Timber Beams and Glued Laminated Timber Beams of Dipteryx panamensis and Hieronyma alchorneoides Wood from Fast-Growth Plantation - Róger Moya; Carolina Tenorio; Angel Navarro-Mora; Freddy Munoz (Drvna Industrija, 2023)
Dipteryx panamensis and Hieronyma alchorneoides are two species of high specific gravity used in reforestation programs in Costa Rica, but they lack products with structural value for commercialization. In order to introduce the wood of these two species in the market, the objective was established to study the behavior of solid timber beams and glued laminated timber beams of two cross sections (2 cm × 10 cm and 2 cm × 15 cm) and establish the design values in bending test. The results showed that the bending design values (fb) ranged from 2 to 26 MPa in glued laminated timber beams, while in solid timber beams, fb ranged from 6 to 15 MPa. In the shear design values (fv), the variation was from 0.29 to 0.67 MPa in glue laminated timber beams and from 1.80 to 2.58 MPa in solid timber beams. It was also found that the D. panamensis beams showed higher values than H. alchornoides beams. Finally, it was established that glued laminated timber beams showed better performance in bending parameters and higher design values, resulting in wider span values, than solid timber beams when used in floor and roof construction.